Centaurea nigrescens (Asteraceae) in the flora of Ukraine: history of research and new data (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: Is there Centaurea nigrescens in the flora of Ukraine? What is the history of the species observations in Ukraine? Location: Ukraine. Materials and methods: field surveys, literature data, herbarium specimens, and analysis of the open databases. Nomenclature: https://powo.science.kew.org/ Results: The article provides data on the history of observations and distribution of Centaurea nigrescens in Ukraine. Literature analysis and revision of herbarium collections allowed to establish that this species has been known in Ukraine since 1809. For two centuries, this species was listed for different regions of Ukraine (in Transcarpathia, in the central and north-eastern parts of Ukraine and in adjacent territories), but herbarium specimens confirmed only localities in Transcarpathia and in the Kharkiv region. In 2023, this species was discovered in the vicinity of Liubotyn City (Kharkiv region, Ukraine). However, C. nigrescens was absent in the latest nomenclatural and floristic lists of the flora of Ukraine. The current distribution of C. nigrescens in Ukraine covers the Zakarpattia and Kharkiv regions. According to morphological features, the plants found in the Kharkiv region are identified as C. nigrescens subsp. pinnatifida. This taxon is listed for the first time for the flora of Ukraine. It is naturally distributed mainly on the Italian Peninsula and listed as alien plant for the Ukrainian flora. C. nigrescens subsp. pinnatifida should be recognized as a neophyte and xenophyte of Mediterranean origin. The studied populations of C. nigrescens subsp. pinnatifida occurred in ecotonic plant communities, such as the edges of oak forests and deforestations, as well as confined to ruderal habitats along roads, on the edge of agricultural lands, etc. This subspecies has successfully naturalized in secondary habitats and is assumed to show a tendency to further spread. Conclusions: the history of the researches and observations of C. nigrescens. in Ukraine were investigated and clarified. The new alien plant was registered in the flora of Ukraine – C. nigrescens subsp. pinnatifida.
Keywords: biodiversity, alien species, neophytes, chorology, plant, morphology, hybrids, Kharkiv region